(untitled) (Economic and Political Thought, 2015)
The new economic order emerging before our very eyes, resulting from the departure from the multilateral principles in favour of selective solutions is a consequence of the implementation of philosophy based on the domination of particular elements over the common ones. Therefore, such solutions are selected which could be called à la carte, because their choice from the universal menu suits own interests of those who still have the most to say in determining global rules. It concerns TFAs which join countries which sometimes have quite divergent approaches to socioeconomic philosophy and practical solutions in the field of economic policy. What binds them firmly, however, is the belief that they should abandon the burden of commitments within the WTO and follow a new path demarcated by the TPP, TTIP or TiSA. The fact that it is really determined by the one who currently has the greatest bargaining power is of course another issue that can also be considered in terms of the balance of benefits and costs of accepting such a situation by weaker partners. As a result, we are dealing with the atomisation of the world exchange in both subjective and directional terms. This last issue in particular, in the context of the increasing role of the Pacific region in the global economy, is a good starting point for further considerations.